2020
DOI: 10.3390/ijms21030773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Combination of Radioimmunotherapy and Immunotherapy in a Melanoma Mouse Model

Abstract: Immunotherapy has changed the oncology landscape during the last decade and become standard of care for several cancers. The combinations of immunotherapy with other treatment modalities are also being investigated. One of the challenges to investigate such combinations is to identify suitable mouse models for the pre-clinical experiments. In the past, we and other researchers showed that murine B16-F10 melanoma in C57Bl6 mice is refractory to treatment with immune checkpoint inhibitors. In this work we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
(23 reference statements)
0
22
1
Order By: Relevance
“…We observed that RIT alone, using either 177 Lu or 225 Ac, did not control tumor growth (Table 1, Figures 2 and 4). This contrasts with our previous studies, where we assessed the cytotoxic effect of the shorter-lived alpha emitter, 213 Bi [12,13]. In those works, we found that both the S91 Cloudman model and the more rapidly dividing B16F10 model were highly susceptible to RIT with 213 Bi.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…We observed that RIT alone, using either 177 Lu or 225 Ac, did not control tumor growth (Table 1, Figures 2 and 4). This contrasts with our previous studies, where we assessed the cytotoxic effect of the shorter-lived alpha emitter, 213 Bi [12,13]. In those works, we found that both the S91 Cloudman model and the more rapidly dividing B16F10 model were highly susceptible to RIT with 213 Bi.…”
Section: Discussioncontrasting
confidence: 95%
“…In this study, we utilized male DBA/2 mice bearing Cloudman S91 tumors, a syngeneic melanoma model [ 20 ], to assess the combination of immunotherapy with long-lived alpha- and beta-emitting RIT. We and others have confirmed the utility of this model in evaluating the effectiveness of immunotherapy alone or in combination with other treatments and have demonstrated anti-PD-1 provides modest tumor control and improved survival [ 13 , 21 , 22 ]. Additionally, we have shown that the combination of anti-PD-1 therapy with RIT using 213 Bi-labeled h8C3, a humanized mAb targeting melanin, slows down tumor growth by 1.5 fold times and improves survival in this model [ 13 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Syngeneic tumor models are also used to investigate the antitumor activity of ICIs, including anti-cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) [39] and anti-programmed death (PD)-1 anti-PD-L1 antibodies [31,40]. For example, using the syngeneic model of immunocompetent B6 mice transplanted with E.G7 hematopoietic cell line or its analogue with PD-L1 deficiency it has been shown that the PD-L1 pathway blockade contributed to the rejection of tumor cells in mice transplanted with both wild-type (WT) E.G7 cells or PD-L1 deficient E.G7 cells in the same degree.…”
Section: Syngeneic Tumor Modelsmentioning
confidence: 99%
“…Thus, the expression of PD-L1 on the cells of TME (either tumor infiltrating leukocytes or stromal cells) may contribute more significantly than the expression of PD-L1 on tumor cells [41]. One of the significant drawbacks of using syngeneic models to evaluate the effectiveness of ICIs is that the rapid Syngeneic tumor models are also used to investigate the antitumor activity of ICIs, including anti-cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) [39] and anti-programmed death (PD)-1 anti-PD-L1 antibodies [31,40]. For example, using the syngeneic model of immunocompetent B6 mice transplanted with E.G7 hematopoietic cell line or its analogue with PD-L1 deficiency it has been shown that the PD-L1 pathway blockade contributed to the rejection of tumor cells in mice transplanted with both wild-type (WT) E.G7 cells or PD-L1 deficient E.G7 cells in the same degree.…”
Section: Syngeneic Tumor Modelsmentioning
confidence: 99%